Exploring the intricate relationship between miRNA dysregulation and breast cancer development: insights into the impact of environmental chemicals - Abolhasanzadeh, Narges; Sarabandi, Sajed; Dehghan, Bahar; Karamad, Vahidreza; Avci, Cigir Biray; Shademan, Behrouz; Nourazarian, Alireza (Frontiers in Immunology, 2024)
Breast cancer stands as the most prevalent form of cancer among women globally, influenced by a combination of genetic and environmental factors. Recent studies have investigated changes in microRNAs (miRNAs) during breast cancer progression and the potential impact of environmental chemicals on miRNA expression. This review aims to provide an updated overview of miRNA alterations in breast cancer and to explore their potential association with environmental chemicals. We will discuss the current knowledge on dysregulated miRNAs in breast cancer, including both upregulated and downregulated miRNAs. Additionally, we will review the influence of environmental chemicals, such as endocrine-disrupting compounds, heavy metals, and air pollutants, on miRNA expression and their potential contribution to breast cancer development. This review aims to advance our understanding of the complex molecular mechanisms underlying miRNA dysregulation in breast cancer by comprehensively examining miRNA alterations and their association with environmental chemicals. This knowledge is crucial for the development of targeted therapies and preventive measures. Furthermore, identifying specific miRNAs affected by environmental chemicals may allow the prediction of individual susceptibility to breast cancer and the design of personalized intervention strategies.